Reflexividad y elección de la escuela por los padres de la clase media en Francia - Van Zanten, Agnès (Revista de Antropología Social, 2007)
This article examines a process, school choice, from a specific perspective, that is the reflexivity of social actors. Based on the analysis of 170 interviews with upper and lower-middle class parents in France and after exploring the consequences of taking into account parents’ capacity to proceed to critical examination of their actions and the distinctive features in that respect of middle-class parents, the author focus on three dimensions of the practical application of this reflexivity. The first concerns parents’ social research on schools for which they use tools and methods similar to those of social researchers but with different goals and a different level of access to information. The second concerns parents’ analysis of the problems of state local schools for which they use criteria similar to those put forward by research studies but interpreted according to their individual interests. The third dimension concerns the analysis of the consequences of school choice. Parents’ use scientific and political arguments to show the tension between individual responsibility and the search for the common good. The conclusion insists on the importance of taking into account parents’ reasoning capacity both to construct more comprehensive interpretative models and to develop a more deliberative democratic society.